The Effects of Mentha × piperita Essential Oil on C. albicans Growth, Transition, Biofilm Formation, and the Expression of Secreted Aspartyl Proteinases Genes - Chahrazed Benzaid; Amine Belmadani; Ryad Djeribi; Mahmoud Rouabhia (MDPI AG, 2019)
The rise in resistance and changes in the spectrum of Candida infections have generated enormous interest in developing new antifungal drugs using natural molecules such as plant essential oils (EOs). Antimicrobial activity against foodborne pathogenic and spoilage microorganisms has been reported for EOs. The goal of this study was to assess the effect of Mentha × piperita essential oil (EO) on C. albicans growth, transition (change from blastospore to hyphae forms), and biofilm formation as well as on the expression of certain virulent genes. We show that whole EO and its vapor attenuated the yeast’s growth, compared to that in the control. The effect of the EO was comparable to that of amphotericin-B (AmB). The EO and its vapor significantly decreased the morphological changes of C. albicans, reduced biofilm formation, and disrupted mature C. albicans biofilms. The effect produced by whole EO on biofilm formation/disruption was notably comparable to that observed with AmB. Exposure of C. albicans to EO and its vapor downregulated the expression of various genes, such as secreted aspartyl proteinases (SAP 1, 2, 3, 9, 10) and hyphal wall protein 1 (HWP1). Altogether, these results provide new insight into the efficacy of Mentha × piperita EO against C. albicans and suggest the potential of Mentha × piperita EO for use as an antifungal therapy in multiple applications.